CLASSROOM ACTION RESEARCH: Using Semantic Mapping in Teaching Descriptive Paragraph - Dahler Dahler (ELT-Lectura, 2015)
This classroom action research conducted to 38 participants at the seventh grade class D of SMPN 29 in2011/2012 academic years. It tries to improve their writing skill by applying semantic mapping strategy. Theresearcher collecting writing tests, observations, field notes, and interview as the instrument. The date reveals that improvement exists after the treatment on the students' writing skill. The data indicates that some factors influenced their improvement. The first was brainstorming process that led them easy to convey and think about the ideas. The second was the categorization process that made them easy to determine kinds of the idea. The third was the mapping process made them easy to write a good descriptive paragraph. The last was the teacher’s roles facilitated them to have an effective class.